Twelve o'clock high [videorecording (DVD)] - King, Henry, 1886-1982; Peck, Gregory, 1916-2003; Marlowe, Hugh, 1911-1982; Merrill, Gary; Jagger, Dean, 1903-1991; Lay, Beirne, Jr., 1909-1982; Bartlett, Sy, 1903-1978 (Twentieth Century Fox Home Entertainment, 2007)
The commander of a U.S. bomber unit in Britain during World War II begins to crack under the strain.